Seasonal changes in foliar calcium oxalate concentrations in conifer and hardwood trees: a potentially bioavailable source of cellular calcium and/or oxalate under stress - Minocha, Rakesh; Long, Stephanie (Frontiers in Forests and Global Change, 2023)
The present study compared seasonal changes in the concentrations of calcium oxalate (CaOx) crystals and total calcium (Ca) in the foliage of red spruce (Picea rubens Sarg.), white pine (Pinus strobus L.), black oak (Quercus velutina L.), and sugar maple (Acer saccharum Marshall) trees. Samples were collected from the same four replicate trees of each species starting in June 2014 through September 2015 for a total of six times for conifers and four times for hardwoods. Calcium oxalate was extracted from tissues using a method developed in our laboratory in 2015. The purity of the extracted CaOx was indicated by an r2 of 0.98 between Ca and oxalate (Ox) for the data pooled across all species and all sampling times. As expected, the concentrations of CaOx varied between species. We hypothesized that the only role of CaOx crystals is to bind excess Ca, so based on this hypothesis the concentrations of CaOx would increase over the growing season both in conifer and hardwood trees, and in conifers, its quantities would be higher in the older relative to the younger needles. However, we found, that for most species, CaOx concentrations were not significantly different from each other for all collection times. In addition, relative to total Ca, the percent of Ca that existed in the form of CaOx varied widely with species, time of collection within a species, and needle age. Thus, no specific trend was observed for CaOx accumulations with changes in seasons. Concentrations of CaOx were indeed higher in older spruce and pine needle. Based on the available literature on this topic and our data, this could mean that CaOx amounts are dynamic and are continuously being adjusted according to the metabolic needs of cells for either Ca or Ox while still performing the function of shedding off excess Ca.